SARS-CoV-2-Specific Memory T Lymphocytes From COVID-19 Convalescent Donors: Identification, Biobanking, and Large-Scale Production for Adoptive Cell Therapy - Ferreras, C.; Pascual-Miguel, B.; Mestre-Durán, C.; Navarro-Zapata, A.; Clares-Villa, L.; Martín-Cortázar, C.; De Paz, R.; Marcos, A.; Vicario, J. L.; Balas, A.; García-Sánchez, F.; Eguizabal, C.; et al. (Frontiers in Cell and Developmental Biology, 2021)
SARS-CoV-2 is causing a second outbreak so the hope for its complete eradication is far from happening. In the absence of effective vaccines, it is mandatory to find effective treatments with low adverse effects able to treat hospitalized patients with COVID-19 disease. In this work, we determined the existence of SARS-CoV-2 specific T cells within the CD45RA- T memory cells from the blood of convalescent donors. Memory T cells can respond quickly to the infection and provide long-term immune protection to reduce the severity of the COVID-19 symptoms. Also, CD45RA- memory T cells confer protection from other pathogens the donors encountered in their life. This is vital to clear other secondary infections usually developed in hospitalized COVID-19 patients. SARS-CoV-2 specific memory T cells were found within all the CD45RA- subsets CD3+, CD4+, CD8+, and in the central memory and effector memory subpopulations. The procedure to obtain the cells is feasible, easy to implement for small scale manufacture, quick and cost-effective involving minimal manipulation, and without GMP condition requirements. This biobank of specific SARS-CoV-2 memory T cells would be immediately available ‘off-the-shelf’ to treat moderate/severe cases of COVID-19 increasing the therapeutic options available for these patients.